Tsunami source uncertainty estimation: the 2011 Japan tsunami - Dettmer, Jan; Hawkins, Rhys; Cummins, Phil R.; Hossen, Jakir; Sambridge, Malcolm; Hino, Ryota; Inazu, Daisuke (© 2016 Blackwell Publishing Ltd, 2016)
This article was published in the Journal of Geophysical Research: Solid Earth [©2016 American Geophysical Union] and the definite version is available at : http://dx.doi.org/10.1002/2015JB012764 The Journal's website is at: http://onlinelibrary.wiley.com/doi/10.1002/2015JB012764/abstract;jsessionid=BF5813B61924FB094F31BC8F213840A1.f02t04